2019
DOI: 10.1186/s13287-019-1470-z
|View full text |Cite
|
Sign up to set email alerts
|

The osteogenic differentiation of human adipose-derived stem cells is regulated through the let-7i-3p/LEF1/β-catenin axis under cyclic strain

Abstract: Background: The Wnt/β-catenin pathway is involved in the osteogenic differentiation of human adipose-derived stem cells (hASCs) under cyclic strain. Very little is known about the role of microRNAs in these events. Methods: Cells were obtained using enzyme digestion methods, and proliferation was detected using Cell Counting Kit 8. Cell cycles and immunophenotypes were detected by flow cytometry. The multilineage potential of hASCs was induced by induction media. Cyclic strain was applied to hASCs (0.5 Hz, 2 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…In prior studies carried out in our laboratory, miR-503-3p expression in hASCs was downregulated during OD in vitro under tensile strain. Our data also showed that there was activation of the W-β pathway as well [6,18]. Based on the result of bioinformation, Wnt2 and Wnt7b, which were activators of the W-β pathway, may be targets of miR-503-3p.…”
Section: Introductionsupporting
confidence: 57%
“…In prior studies carried out in our laboratory, miR-503-3p expression in hASCs was downregulated during OD in vitro under tensile strain. Our data also showed that there was activation of the W-β pathway as well [6,18]. Based on the result of bioinformation, Wnt2 and Wnt7b, which were activators of the W-β pathway, may be targets of miR-503-3p.…”
Section: Introductionsupporting
confidence: 57%
“…Lymphoid enhancer-binding factor 1 (LEF1) is a transcription factor involved in many diseases [3][4][5][6] . It belongs to the high-mobility group family that regulates gene expression by inducing structural alteration in the DNA helix 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Both transcription factor 7 (TCF-7) and lymphoid enhancer binding factor 1 (LEF1) are members of the T cell factor/lymphoid enhancer-binding factor family of high mobility group (HMG) box transcriptional activators. LEF1, a proxy for active Wnt signaling, is activated not only by cyclic strain and physiological tensile strain, but also in tissue expansion ( Thomas et al, 2011 ; Luo et al, 2019 ). The LEF1 and Wnt signaling pathways are involved in hair cell differentiation and follicle morphogenesis ( Lien et al, 2014 ; Adam et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%